Chitosan increases Pinus pinaster tolerance to the pinewood nematode (Bursaphelenchus xylophilus) by promoting plant antioxidative metabolism - Nunes da Silva, Marta; Santos, Carla S.; Cruz, Ana; López-Villamor, Adrián; Vasconcelos, Marta W. (Scientific reports, 2021)
The pine wilt disease (PWD), for which no effective treatment is available at the moment, is a constant threat to Pinus spp. plantations worldwide, being responsible for significant economic and environmental losses every year. It has been demonstrated that elicitation with chitosan increases plant tolerance to the pinewood nematode (PWN) Bursaphelenchus xylophilus , the causal agent of the PWD, but the biochemical and genetic aspects underlying this response have not been explored. To understand the influence of chitosan in Pinus pinaster tolerance against PWN, a low-molecular-weight (327 kDa) chitosan was applied to mock- and PWN-inoculated plants. Nematode population, malondialdehyde (MDA), catalase, carotenoids, anthocyanins, phenolic compounds, lignin and gene expression related to oxidative stress (thioredoxin 1, TRX ) and plant defence (defensin, DEF , and a-farnesene synthase, AFS ), were analysed at 1, 7, 14, 21 and 28 days post-inoculation (dpi). At 28 dpi, PWN-infected plants elicited with chitosan showed a sixfold lower nematode population when compared to non-elicited plants. Higher levels of MDA, catalase, carotenoids, anthocyanins, phenolic compounds, and lignin were detected in chitosan-elicited plants following infection. The expression levels of DEF gene were higher in elicited plants, while TRX and AFS expression was lower, possibly due to the disease containment-effect of chitosan. Combined, we conclude that chitosan induces pine defences against PWD via modulation of metabolic and transcriptomic mechanisms related with plant antioxidant system.